Influence of agrometeorological variables on the severity of maize white spot and its effect on yield in tropical and subtropical regions - Rodriguez Roa, Andrea Onelia [UNESP]; de Lima, Rafael Fausto [UNESP]; Fantin, Gisèle Maria; Duarte, Aildson Pereira; de Souza Rolim, Glauco [UNESP] (Springer Nature, 2025)
Maize production is affected by several biotic and abiotic factors, with diseases being a major cause of yield and quality loss. The maize white spot (MWS) is one of the most important diseases and is widespread in tropical and subtropical production areas. Its development depends on the interactions among plants, pathogens and environmental conditions. Understanding the environmental conditions that favor disease development is essential for predicting disease occurrence in different regions and for implementing effective crop management strategies. This study evaluated the relationships between agrometeorological variables and the severity of MWS, as well as the impact of the disease on maize yield under field conditions. The analysis was based on 25 years of MWS severity and yield data collected from 29 production sites in São Paulo, Brazil. Statistical approaches include correlation analysis, linear regression models, and pattern identification in the data distribution. The observed trend suggests that the maize yield decreases by approximately 45.7 kg ha−1 (≈ 1%) for each 1% increase in MWS severity. The variables most strongly associated with increased MWS severity are relative humidity (> 55%), soil moisture (> 0.3), mean temperature (15–22 °C), maximum temperature (20–30 °C), diurnal temperature range (8–16 °C), and wind speed (< 3 m s−1). These findings improve the understanding of the effects of the environment on disease progression, expand the knowledge of key factors and reveal new associations. The results provide valuable input for predictive models and management strategies to mitigate the impact of MWS on maize production.